UKURAN PERUSAHAAN MEMODERASI CURRENT RATIO (CR) DAN RETURN ON ASSETS (ROA) PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN - Salma Tsamarah Nurjannah; Zaky Machmuddah (Universitas Budi Luhur, 2024)
The objective of this study is to assess the influence of Current Ratio (CR) and Return on Assets (ROA) on the stock prices of food and beverage companies authenticated by the Indonesia Stock Exchange, and to explore whether the correlation between these variables can be influenced by the size of the company. The research focuses on manufacturing companies within the food and beverage sub-sector during the timeframe from 2019 to 2022. Employing a quantitative research approach with secondary data, the population was chosen through purposive sampling, involving 25 samples out of 84 manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange between 2019 and 2022. The analysis method utilized Partial Least Square (PLS) through the Warp PLS application. The findings indicate that ROA exerts a positive and significant impact on stock prices, and company size moderates the relationship between ROA and stock prices. On the other hand, CR negatively affects stock prices without statistical significance, and company size does not moderate the association between CR and stock prices.